The ability of critical thinking and problem solving prospective biology teacher to solve biological Olympiad questions - Eka Trisianawati; Tesa Manisa (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
It takes careful preparation to answer questions with a high difficulty level regarding the trainers' readiness and the student's readiness in the Biology Olympiad Coaching elective course. Critical thinking skills and problem-solving are needed in solving these Olympiad questions. This study aims to analyse biology teacher candidates' critical thinking skills and problem-solving in solving biology Olympiad questions. This study used a quasi-experimental method using the Reading, Questioning, and Answering (RQA) learning model. The dependent variable to be measured is the ability to think critically and solve problems for prospective Biology teacher students. This research was carried out in the even semester of the 2021/2022 academic year in two classes in the Biology Olympiad Development course at IKIP PGRI Pontianak. The research sample was taken in a saturated manner. Before being given to students, all questions were validated by experts and then continued with the research implementation to obtain data. The normality and homogeneity of research data were then tested. Finally, the research hypothesis was tested using one-way ANCOVA. The study results show that the RQA learning model can empower critical thinking skills and solve problems for prospective teacher students. The RQA learning model can be an effective solution to deal with the advancement of 21st century education.Abstrak Dibutuh persiapan yang matang untuk menjawab soal dengan tingkat kesulitan yang tinggi, baik dari segi kesiapan pelatih maupun kesiapan siswanya pada mata kuliah pilihan Pembinaan Olimpiade Biologi. Kemampuan berpikir kritis dan pemecahan masalah diperlukan dalam penyelesaian soal olimpiade ini. Penelitian ini bertujuan untuk menganalisis kemampuan berpikir kritis dan pemecahan masalah mahasiswa calon guru biologi dalam menyelesaikan soal olimpiade biologi. Penelitian ini menggunakan metode kuasi eksperimen menggunakan model pembelajaran Reading, Questioning, and Answering (RQA). Variabel terikat yang akan diukur yakni kemampuan berpikir kritis dan pemecahan masalah mahahsiswa calon guru Biologi. Penelitian ini dilaksanakan pada semester genap tahun ajaran 2021/2022 di dua kelas pada mata kuliah Pembinaan Olimpiade Biologi IKIP PGRI Pontianak. Sampel penelitian diambil secara jenuh. Sebelum diberikan kepada siswa, seluruh soal telah divalidasi oleh ahli kemudian dilanjutkan dengan pelaksanaan penelitian hingga didapatlah data penelitian. Data penelitian kemudian diuji normalitas dan homogenitasnya dan yang terakhir diuji hipotesis penelitian menggunakan one way ANCOVA. Hasil penelitian menunjukkan jika model pembelajaran RQA dapat memberdayakan kemampuan berpikir kritis dan memecahkan masalah mahasiswa calon guru. Model pembelajaran RQA dapat menjadi salah satu solusi yang efektif untuk menghadapi kemajuan pendidikan abad 21.